Role of Electronic Relaxation Rates in the Casimir Force between High-Tc Superconductors - Shunashi G. Castillo-López; Carlos Villarreal; Giuseppe Pirruccio; Raúl Esquivel-Sirvent (Universe, 2021)
We revisit the problem of the Casimir force between high-Tc superconductors below and above the critical temperature for the superconducting transition. Ceramic superconductors exhibit a different temperature dependence of the reflectivity when switching from the normal to the superconducting state. We leverage this unique characteristic with respect to ordinary metals to claim that these kind of materials can prove useful as an alternative system where the long-standing discussion on the role of electronic relaxation can be addressed. Furthermore, we show that the two main damping mechanisms associated with free and mid-infrared electrons dominate at very distinct scales, meaning that they can be considered separately when the Casimir force is measured as a function of slab distance. This facilitates the experimental identification of the role of the two electronic relaxation contributions to the force.